Distribution of pathogens and antimicrobial resistance in bacteraemia according to hospitalization duration: a nationwide surveillance study in Switzerland. (December 2021) - Buetti, Niccolò; Marschall, Jonas; Timsit, Jean-François; Atkinson, Andrew; Kronenberg, Andreas; Sommerstein, Rami; ,; Burnens, A.; Cherkaoui, A.; Corradi, C.; Dubuis, O.; Viollier, A.G.; et al.
Abstract: Objectives: Changing microorganism distributions and decreasing antibiotic susceptibility with increasing length of hospital stay have been demonstrated for the colonization or infection of selected organ systems. We wanted to describe microorganism distribution or antibiotic resistance in bacteraemia according to duration of the hospitalization using a large national epidemiological/microbiological database (ANRESIS) in Switzerland. Methods: We conducted a nationwide, observational study on bacteraemia using ANRESIS data from 1 January 2008 to 31 December 2017. We analysed data on bacteraemia from those Swiss hospitals that sent information on a regular basis during the entire study period. We described the pathogen distribution and specific trends of resistance during hospitalization for Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Serratia marcescens and Staphylococcus aureus . Results: We included 28 318 bacteraemia isolates from 90 Swiss hospitals. The most common aetiology was E. coli (33.4%, 9459), followed by S. aureus (16.7%, 4721), K. pneumoniae (7.1%, 2005), Enterococcus faecalis (5.2%, 1473), P. aeruginosa (4.3%, 1228), Streptococcus pneumoniae (4.3%, 1208) and Enterococcus faecium (3.9%, 1101). We observed 489 (1.73%) S. marcescens isolates. We observed an increasing trend for E. faecium (from 1.5% at day 0 to 13.7% at day 30; p < 0.001), K. pneumoniae (from 6.1% to 7.8%, p < 0.001) and P. aeruginosa (from 2.9% to 13.7%, p < 0.001) with increasing duration of hospitalization; and decreasing trends for E. coli (from 41.6% to 21.6%; p < 0.001) and S. aureus (p < 0.001). Ceftriaxone resistance among E. coli remained stable for the first 15 days of hospitalization and then increased. Ceftriaxone resistance among K. pneumoniae and S. marcescens and oxacillin resistance among S. aureus increased linearly during the hospitalization. Cefepime resistance among P. aeruginosa remained stable during the hospitalization. Discussion: We showed that hospitalization duration is associated with a species- and antibiotic class-dependent pattern of antimicrobial resistance.